Conquering the crush: A novel tool for holding crocodilian jaws open - Miriam Boucher; Thomas R. Rainwater; Michael Stoner; Luis Sigler; Stefanie L. Whitmire; James T. Anderson (Wildlife Society Bulletin)
Abstract Crocodilians have diverse snout shapes ranging from the long, narrow snouts of the Indian gharial (Gavialis gangeticus) to the broad snout of the American alligator (Alligator mississippiensis). In addition, crocodilians possess the strongest bite force of all extant animals, with recorded values for adult alligators exceeding 9 kilonewtons (kN). Jaw‐closing pressure poses a challenge and safety risk for people working with crocodilians, such as veterinarians, wildlife managers, and researchers who must safely access the oral cavity to perform veterinary procedures, health assessments, hook removals, or sample collection. Conventionally, polyvinyl chloride (PVC) or metal tubes (pipes) placed longitudinally into the mouth have been used to hold crocodilian jaws open for such operations. The short sections of opaque pipe can cause oral irritation, obscure the palate and tongue, and restrict access to the oral cavity and palatal valve. In conjunction with a project investigating the diet of alligators in the southeastern United States, we identified a need to create an efficient tool to allow safe and direct access to the alligator oral cavity. We built 2 versions of a device for holding alligator jaws open that are adjustable to accommodate different gape sizes. The device allows for safe positioning within the mouth, includes safety considerations for device failure, and is adaptable to both widen and collapse the gape of the mouth. We successfully deployed and recovered the device on 76 wild alligators ranging in total length from 120 to 329 cm. We also performed mechanical tests in the laboratory to assess the maximum force the devices and associated materials can safely withstand, as well as the conditions under which the devices fail. Our medium‐duty and heavy‐duty device designs withstood forces up to 6 kN and 18 kN, respectively. We observed no material fracture in the devices but did observe deformations of materials used during laboratory testing. The device is an inexpensive and effective tool for veterinarians, wildlife researchers, and managers who need to hold open the jaws of crocodilians safely.